1985
DOI: 10.1021/bi00336a001
|View full text |Cite
|
Sign up to set email alerts
|

ADP/ATP carrier protein from beef heart mitochondria has high amounts of tightly bound cardiolipin, as revealed by phosphorus-31 nuclear magnetic resonance

Abstract: An unusual binding of cardiolipin to the ADP/ATP carrier has been found, which is distinguished by the relatively large amount and by the tightness of binding. High-resolution 31P NMR studies on the detergent-solubilized ADP/ATP carrier from beef heart mitochondria revealed narrow signals from phosphatidylcholine and phosphatidylethanolamine and a broadened signal of 30-40-Hz line width, suggestive of cardiolipin. Line broadening of this magnitude is to be expected when tumbling of the whole protein-detergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
190
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(200 citation statements)
references
References 26 publications
9
190
0
1
Order By: Relevance
“…Many IMM proteins have CL-binding domains, thus limiting free exchange and redistribution of the phospholipid to the OMM. [28][29][30][31][32][33][34][35][36] In some of these proteins, CL molecules are buried 'deeply' within multimeric protein complexes (like in electron-transporting respirasomes 35,36 ), whereas in the others the affinity and accessibility of CL for translocations seem to be less restricted (e.g., TIM40 37 ). Although the exact amounts of CL in the two pools -free versus bound -have not been established, it is likely that in normally functioning mitochondria, the majority of the IMM CLs is not readily mobilized.…”
Section: Discussionmentioning
confidence: 99%
“…Many IMM proteins have CL-binding domains, thus limiting free exchange and redistribution of the phospholipid to the OMM. [28][29][30][31][32][33][34][35][36] In some of these proteins, CL molecules are buried 'deeply' within multimeric protein complexes (like in electron-transporting respirasomes 35,36 ), whereas in the others the affinity and accessibility of CL for translocations seem to be less restricted (e.g., TIM40 37 ). Although the exact amounts of CL in the two pools -free versus bound -have not been established, it is likely that in normally functioning mitochondria, the majority of the IMM CLs is not readily mobilized.…”
Section: Discussionmentioning
confidence: 99%
“…Once produced, ATP is transported across the IM by AAC2 in exchange for ADP. Both AAC2 and the ATP synthase are structurally associated with CL (Beyer and Klingenberg, 1985;Eble et al, 1990;Nury et al, 2005) as opposed to simply embedded in membranes that happen to contain CL. Very little is known about how so-called structural phospholipids are incorporated into the final tertiary and/or quaternary structure of membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the effect of peroxidized cardiolipin on the MPT induction is modulated by ligands and inhibitors of ADP carrier, points to an involvement of this protein system in this process. Cardiolipins were shown to be tightly associated with ANT with a stoichiometry of 3 cardiolipins per protein monomer [32]. It was suggested that interactions between two monomers of the ANT is mediated by cardiolipins, which could stabilize the dimer and structure, by controlling the conformational changes and participate in triggering a concerted ADP/ATP exchange [33].…”
Section: Discussionmentioning
confidence: 99%